Professional Training Model for Prospective Mutawif among Youth Delegates - Aminatul Ummah; Mutrofin Mutrofin; Bobby Rachman Santoso; Salma Sayidatul Ula; Shofi Salsabila; Rohmatul Hadi; Rizky Setiawan; Moch Irgi Fahlevi; Akbar Abdul Latifef; Chusnul Chotimah (Al-Qalam Institute, 2025)
The implementation of Hajj and Umrah rituals requires professional guidance due to the procedural complexity of manasik and the increasingly diverse socio-demographic backgrounds of Indonesian pilgrims. This community service project therefore aims to strengthen the professional capacity of prospective mutawifs among East Java youth representatives through a structured and participatory training model. The program employed a Participatory Action Research (PAR) approach, engaging participants as active collaborators in needs assessment, training design, implementation, and evaluation. Data were collected through pre- and post-training assessments, observation during manasik simulations, reflective discussions, and performance evaluations. The findings indicate a significant improvement in participants’ mastery of fiqh al-manasik and ritual procedures. Participants also demonstrated enhanced communication competence in guiding elderly pilgrims and managing group dynamics. Conflict resolution and crisis-response skills improved through scenario-based simulations. Moreover, the training strengthened ethical awareness, service orientation, and spiritual responsibility as mutawifs. Participants reported increased self-confidence and readiness to serve in real pilgrimage contexts. This program contributes a replicable youth-based mutawif capacity-building model that integrates technical, interpersonal, and spiritual competencies. It is recommended that religious institutions and Hajj service providers adopt sustainable, competency-based training frameworks to prepare future professional mutawifs.